Changes in immune cell populations during acclimatization to high altitude - Kathy Pham; Abel Vargas; Shyleen Frost; Saheli Shah; Erica C. Heinrich (Physiological Reports)
Abstract The immune response to acute hypoxemia may play a critical role in high‐altitude acclimatization and adaptation. However, if not properly controlled, hypoxemia‐induced inflammation may exacerbate high‐altitude pathologies, such as acute mountain sickness (AMS), or other hypoxia‐related clinical conditions. Several studies report changes in immune cell subsets at high altitude. However, the mechanisms underlying these changes, and if these alterations are beneficial or maladaptive, remains unknown. To address this, we performed multiparameter flow cytometry on peripheral blood mononuclear cells (PBMCs) collected throughout 3 days of high‐altitude acclimatization in healthy sea‐level residents (n = 20). Additionally, we conducted in vitro stimulation assays to test if high‐altitude hypoxia exposure influences responses of immune cells to subsequent inflammatory stimuli. We found several immune populations were altered at high altitude, including monocytes, T cells, and B cells. Some changes in immune cell populations are potentially correlated with AMS incidence and severity. In vitro high‐altitude PBMC cultures stimulated with lipopolysaccharide (LPS) showed no changes in pro‐inflammatory cytokine production after 1 day at high‐altitude. However, by day three pro‐inflammatory cytokine production in response to LPS decreased significantly. These results indicate that high‐altitude exposure may initiate an inflammatory response that encompasses innate immune sensitization, with adaptive immune suppression following acclimatization.